Media censorship and the Government - Abakare, Chris (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Throughout the world commentators and journalists have an important responsibility to reliably inform the general public of the latest stories, events, and opinions. While doing so, they also have the added responsibility of protecting their sources. However, while media outlets provide myriad benefits, the advances in connectivity and wealth may come at the expense of misinformation, fraud and the country’s stability. Today, due to the above, governments around the world are tightening control over devise media houses using claims of "fake news" to suppress freedom of speech. There is no doubt that due to the private ownership nature of most media house in Nigeria, misinformation, bribery, censorship and harassment is possible. In this work, I proposed some sanctions on the freedom of the press that are directly or indirectly related to the national interest. I expressed this view in favour of the fact that there are some cases where the government attempts to constrain freedom of speech when there is a genuine threat to national security. Though I caution that this proposal does not apply to tyrant government.